A DAI 38. fejezetének forrásáról - Kristó Gyula (Acta Universitatis Szegediensis : acta historica, 2005)
Almost a decade ago István Kapitánffy published his theory that the source of chapter 38 of the DAI, which chapter deals with the Hungarian history of the 9th century, goes back to the reports of Byzantian legates. The author of this study, analyzing the DAI, refutes this theory, proving that the elements of this chapter came from Hungarian roots, especially from the middle of the 10th century.